2018
DOI: 10.1038/s41443-018-0024-8
|View full text |Cite
|
Sign up to set email alerts
|

An initial study on the effect of functional electrical stimulation in erectile dysfunction: a randomized controlled trial

Abstract: Erectile dysfunction (ED) affects approximately 150 million men worldwide. Functional electrical stimulation (FES) therapy has shown a high regenerative capacity for smooth muscle cells and, therefore, is being increasingly adopted. FES can be a beneficial treatment option when the cause of ED is related to degeneration of cavernous smooth muscle. To evaluate the impact of FES on erectile function in men with erectile dysfunction. Twenty-two patients with ED participated in this randomized clinical trial. Part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 15 publications
0
7
0
2
Order By: Relevance
“…This is consistent with the findings of previous studies. For instance, Carboni et al ( 19 ) reported improvement in erectile function in individuals with ED following 4-weeks of functional electrical stimulations. A similar finding has been reported by Kayigil et al ( 33 ) and Van Kampen et al ( 18 ), who concluded that electrical stimulation plays an important role in the rehabilitation of ED.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This is consistent with the findings of previous studies. For instance, Carboni et al ( 19 ) reported improvement in erectile function in individuals with ED following 4-weeks of functional electrical stimulations. A similar finding has been reported by Kayigil et al ( 33 ) and Van Kampen et al ( 18 ), who concluded that electrical stimulation plays an important role in the rehabilitation of ED.…”
Section: Discussionmentioning
confidence: 99%
“…Sample size and study population : The sample size was calculated using the G*Power version 3.9.1. The Effect Size (ES) used for calculating the sample size was obtained from the previous study ( 19 ) using the International Index of Erectile Function (IIEF-5) primary outcome. The probability level (α), the power (p) and the Effect Size (ES) used for the calculation were then set at 0.05, 0.95 and 3.3 respectively which yielded a sample size of 4 participants per group (total sample size was 8) using independent ttest for between-group analysis.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…As intervenções fisioterapêuticas fornecem métodos não invasivos e indolores, que associados à compreensão da fisiologia da ereção buscam beneficiar os tratamentos para DE. O método FES tem demonstrado um efeito regenerativo sobre o endotélio, com a liberação de óxido nítrico, nesse sentido, Carboni et al (2018) configuraram um estudo para contribuir com a hipótese da regeneração da musculatura lisa do corpo cavernoso e resultar no retorno venoso da função erétil. No estudo com 22 pacientes, com intervenção de FES (50Hz/500µs) por um total de 4 semanas, revelou o método estatisticamente significativo na função erétil, além de benéfico na qualidade de vida.…”
Section: Eletroestimulação Funcionalunclassified